The Influence of Institutional Ownership, Managerial Ownership, Firm Size, and Leverage on Financial Distress in Transportation and Logistics Sector Companies Listed on the Indonesian Stock Exchange (BEI) 2020-2022 - Suryandari Sedyo Utami; Rofi’ah; Silvia Avira; Endang Setyaningsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The aim of this research is to determine the influence of institutional ownership, managerial ownership, independent board of commissioners, company size and leverage on financial distress. The population used in this research is transportation and logistics companies listed on the Indonesia Stock Exchange (BEI) in 2020-2022. Using the purposive sampling method, 10 companies with a total of 30 samples were obtained that met the criteria. The types and sources of data used are quantitative data and secondary data. The data analysis technique uses multiple linear regression analysis using the SPSS version 26 application. The results of this research include institutional ownership, managerial ownership, and have no effect on financial distress. Company size has a positive effect on financial distress. Leverage has a significant negative effect on financial distress. Simultaneously, institutional ownership, managerial ownership, company size and leverage influence financial distress in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period.